2021
DOI: 10.1155/2021/5575928
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cytokine Storm in COVID-19: A Role of Online Hemodiafiltration with Asymmetric Cellulose Triacetate in Maintenance Hemodialysis Patients—A Report of 10 Cases

Abstract: Early reports have suggested that maintenance hemodialysis (MHD) patients could be more susceptible to a severe course of COVID-19. Among the therapeutic approaches, the use of drugs that reduce the cytokine storm characteristic of this disease has been proposed. Some dialyzers, such as the new generation of asymmetric cellulose triacetate (ATA) membranes, could favor the effective elimination of medium-sized molecules and other inflammatory mediators. In this case series, we describe in depth the clinical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Tarakcioǧlu et al [40] evaluated cytokines removal in 21 stable CHD patients treated with low-flux HD and did not find any difference as to IL-1 beta, IL-6, TNF-alpha, and sIL-2R concentrations between pre-and post-HD specimens. De la Flor et al [41] published a case series of 10 CHD patients affected by SARS-CoV-2 who underwent post-dilution OLHDF with ATA. The authors found a higher IL-6 decrease after 14 days in survivors, although no IL-6 RR was determined and there was not a control group [41].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Tarakcioǧlu et al [40] evaluated cytokines removal in 21 stable CHD patients treated with low-flux HD and did not find any difference as to IL-1 beta, IL-6, TNF-alpha, and sIL-2R concentrations between pre-and post-HD specimens. De la Flor et al [41] published a case series of 10 CHD patients affected by SARS-CoV-2 who underwent post-dilution OLHDF with ATA. The authors found a higher IL-6 decrease after 14 days in survivors, although no IL-6 RR was determined and there was not a control group [41].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We conducted this meta-analysis on overall 31 909 COVID-19 patients from 147 studies. 2 , 4 - 7 , 9 - 18 , 24 …”
Section: Resultsmentioning
confidence: 99%
“… 29 In a report of 10 maintenance HD patients, NLR and LCR were associated with the severe form and mortality of COVID 19. 30 Another study conducting on 62 HD patients showed that higher NLR was associated with the most severe form of COVID-19. 31 In line with the literature, mortality was associated with a lower LCR but higher NLR in our study group.…”
Section: Discussionmentioning
confidence: 99%